2013
DOI: 10.2134/agronj2012.0343
|View full text |Cite
|
Sign up to set email alerts
|

Dryland Malt Barley Yield and Quality Affected by Tillage, Cropping Sequence, and Nitrogen Fertilization

Abstract: Malt barley (Hordeum vulgare L.) yield and quality have been evaluated using various cultivars and N rates but little is known about the eff ects of tillage and cropping sequence. We evaluated the eff ects of tillage, cropping sequence, and N fertilization on dryland malt barley yield, grain characteristics, N uptake, and N use-effi ciency from 2006 to 2011 in eastern Montana. Treatments were no-till continuous malt barley (NTCB), no-till malt barley-pea (Pisum sativum L.) (NTB-P), no-till malt barley-fallow (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(80 citation statements)
references
References 31 publications
5
71
2
2
Order By: Relevance
“…As with biomass N, N supplied by pea may have increased annualized grain N removal in D-C-D-P, D-D-C-P, and D-F-D-P in the ecological and traditional practices. Increased biomass and grain N uptake with crop rotations containing pea with spring wheat and barley compared with continuous spring wheat and barley have been reported by several researchers (Lenssen et al, 2007b;Sainju et al, 2013Sainju et al, , 2015.…”
Section: Annualized Crop Biomass and Grain Nitrogenmentioning
confidence: 84%
“…As with biomass N, N supplied by pea may have increased annualized grain N removal in D-C-D-P, D-D-C-P, and D-F-D-P in the ecological and traditional practices. Increased biomass and grain N uptake with crop rotations containing pea with spring wheat and barley compared with continuous spring wheat and barley have been reported by several researchers (Lenssen et al, 2007b;Sainju et al, 2013Sainju et al, , 2015.…”
Section: Annualized Crop Biomass and Grain Nitrogenmentioning
confidence: 84%
“…The amount of N fertilizer was relatively lower in NTB‐P than in CTBN and NTBN due to additional N supplied by pea residue. Pea, being a legume with higher N concentration or lower C/N ratio, decomposes more rapidly than malt barley, a nonlegume, and therefore increases soil mineral N content, which reduces the N fertilization rate to succeeding crops (Mosier et al, 2006; Sainju et al, 2013). As a result, CO 2 emissions due to N fertilization was lower in NTB‐P than in CTB‐N and NTB‐N.…”
Section: Discussionmentioning
confidence: 99%
“…The N:P ratio of YR3 barley was higher in plus-N canola controls than in the YR1 faba bean and pea treatments in 3 of 4 site-years (Table 10). Studies of malt barley have shown that malt barley grain yield, protein concentration, N uptake and biomass increase as N fertilizer rates increase (O'Donovan et al 2011;Sainju et al 2013). O'Donovan et al (2011) noted that malt barley varieties vary in their response to N rate, and increase in protein concentration in response to N rate was more pronounced with AC Metcalfe than with CDC Copeland.…”
Section: Nitrogen Additionsmentioning
confidence: 99%